Implementing the Law of khulʿ in Egypt: Tensions and Ambiguities in Muslim Family Law - Lindbekk, Monika (Hawwa, 2020)
This article aims to contribute to the growing scholarly literature on the implementation of shariʿa-based family law codes by describing and analyzing the gender implications of religiously inspired judicial activism in relation to judicial divorce through khulʿ. The article highlights two functions played by family court judges and other legal professionals. First, I argue that Egyptian family court judges and other court personnel, such as court experts and court-appointed arbiters from al-Azhar, enjoy considerable discretion in interpreting and implementing the personal status codes. Second, the article argues that legal professionals sometimes use the court and other legal spaces as a platform to articulate alternative visions of family and marriage, as well as to voice anxieties over a perceived increase in female-initiated divorce. The article situates these contradictory practices against the background of the contestation of early twenty-first-century reforms, which challenged male authority in the family, in particular the 2000 law of judicial khulʿ.